Diagnostic test accuracy of point-of-care procalcitonin to diagnose serious bacterial infections in children - Thomas Waterfield; Julie-Ann Maney; Mark D Lyttle; James P McKenna; Damian Roland; Michael Corr; Bethany Patenall; Michael D Shields; Kerry Woolfall; Derek Fairley; On behalf of Paediatric Emergency Research in the UK and Ireland (PERUKI) (BMC, 2020)
Abstract Background The National Institute for Health and Care Excellence (NICE) have called for research into the role of biomarkers, and specifically procalcitonin (PCT), for the early diagnosis of serious bacterial infections (SBI) in children. The aim of this study was to compare the diagnostic test accuracy of C-reactive protein (CRP) and PCT for the diagnosis of SBI in children. Methods Data was collected prospectively from four UK emergency departments (ED) between November 2017 and June 2019. Consecutive children under 18 years of age with fever and features of possible sepsis and/or meningitis were eligible for inclusion. The index tests were PCT and CRP and the reference standard was the confirmation of SBI. Results 213 children were included in the final analysis. 116 participants (54.5%) were male, and the median age was 2 years, 9 months. Parenteral antibiotics were given to 100 (46.9%), three (1.4%) were admitted to a paediatric intensive care unit and there were no deaths. There were ten (4.7%) confirmed SBI. The area under the curve for PCT and CRP for the detection of SBI was identical at 0.70. Conclusions There was no difference in the performance of PCT and CRP for the recognition of SBI in this cohort. Trial registration Registered at https://www.clinicaltrials.gov (trial registration: NCT03378258 ) on the 19th of December 2017.